2023
DOI: 10.1186/s12939-022-01806-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on the impact of austerity on healthcare access in the European Union: rethinking austerity for the most vulnerable

Abstract: Background There is consensus that the 2008 financial and economic crisis and related austerity measures adversely impacted access to healthcare. In light of the growing debt caused by the COVID-19 crisis, it is uncertain whether a period of austerity will return. Objective This study aims to provide a structured overview of the impact of austerity policies in the EU-28 zone, applied in response to the Great Recession, on access to health care for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Cuts to public health and healthcare budgets have a direct effect on service provision and waiting times. Indirect effects, via increasing levels of unemployment, poverty and cost of living, make life more difficult for people with long-term health conditions 11 13. A clear link has been demonstrated between deprivation and living in a cold and or damp house and the likelihood of having frequent acute exacerbations of COPD 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuts to public health and healthcare budgets have a direct effect on service provision and waiting times. Indirect effects, via increasing levels of unemployment, poverty and cost of living, make life more difficult for people with long-term health conditions 11 13. A clear link has been demonstrated between deprivation and living in a cold and or damp house and the likelihood of having frequent acute exacerbations of COPD 6.…”
Section: Discussionmentioning
confidence: 99%
“…A second question also arises regarding appropriate training, support and equipment, to allow clinicians to ensure they are providing annual reviews which meet the British Thoracic Socitey (BTS) guidelines. The combination of the austerity measures and COVID-19 pandemic has had a huge negative effect on clinical resources and clinical staff time and is likely to contribute to inadequate COPD reviews 11 13 16. Another consideration is the risk that the review becomes a ‘tick box’ exercise limiting the benefit to individual patients?17 18?…”
Section: Discussionmentioning
confidence: 99%
“…When considering the contribution of behaviour, mindset and incentives to access equity in rare diseases, it is important to look across all stakeholders, notably healthcare providers, policymakers, industry and the patient community. Faced with an ageing population with associated comorbidities and complexities, and with growing healthcare demand, providers and policymakers may adopt a 'savings mindset' and freeze budgets [25] , but this is counterproductive for access equity. Short-termism may mean restricted allocation of funding for innovative and preventive therapies, and resource allocation may occur without detailed knowledge of the issues [26] .…”
Section: Behavioural Change Mindset and Incentivesmentioning
confidence: 99%
“…Short-termism may mean restricted allocation of funding for innovative and preventive therapies, and resource allocation may occur without detailed knowledge of the issues [26] . A behavioural focus on reducing costs while maintaining the current system may result in 'quick fix' decisions being implemented without adequate understanding of potentially adverse long-term implications [25] . This is unhelpful and may be detrimental to access equity.…”
Section: Behavioural Change Mindset and Incentivesmentioning
confidence: 99%
“…Multiple studies have reinforced the impact of the economic recession on healthcare systems and their deterioration if austerity measures are imposed, impacting infant mortality rates (IMR) and perinatal mortality rates (PMR) across Europe,11 12 among others, explained by decreased access to healthcare,13–15 increased stress,16 adverse mental health17 18 and unhealthy behaviours (eg, alcohol usage)19 among pregnant women. Previous studies reported that the Great Recession was associated with a significant increase in low birth weight12 and indicated a reverse in downward trends of IMR, PMR and neonatal mortality, mainly determined by long-term unemployment and income reduction11 (countercyclical fluctuation), thus, socioeconomic indicators.…”
Section: Introductionmentioning
confidence: 99%